2009
DOI: 10.1089/end.2008.0392
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Double Percutaneous Endolaparoscopic Extraction of Large Continent Urinary Reservoir Stones—A New Minimally Invasive Approach

Abstract: Double percutaneous endolaparoscopic stone extraction is a safe, effective, and minimally invasive method of managing continent urinary reservoir stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In 2009, Natalin et al [18] reported a percutaneous technique with a laparoscopic entrapment bag managing stones in 5 patients with continent reservoirs. Recently, Breda et al [19] described percutaneous cystolithotomy for calculi in reconstructed bladders by basketing and ultrasonic lithotripsy.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Natalin et al [18] reported a percutaneous technique with a laparoscopic entrapment bag managing stones in 5 patients with continent reservoirs. Recently, Breda et al [19] described percutaneous cystolithotomy for calculi in reconstructed bladders by basketing and ultrasonic lithotripsy.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the area of bladder substitution have enabled patients to maintain an excellent health‐related quality of life following urinary diversion, but diversion‐associated urolithiasis remains a problem for these patients. Fortunately, advances in endourological equipment and techniques have greatly reduced the morbidity of this common problem (Table 1, [44–52]). Prevention of recurrent stones with correction of metabolic abnormalities, increased fluid intake, pouch irrigation protocols, and prophylaxis against recurrent infections are critical steps in avoiding recurrent stones.…”
Section: Discussionmentioning
confidence: 99%
“…The use of entrapment bags have been described in Indiana pouches and augmented bladders by Lam et al [7] and in urinary reservoirs with a closed urethra by Natalin et al [8]. In this article, we describe the percutaneous access with an amplatz sheath and the use of an entrapment bag to capture a large volume of stones before cystolithotripsy in a normal bladder without a closed urethra.…”
Section: Introductionmentioning
confidence: 94%